Sistem Pendukung Keputusan Untuk Menentukan Status Prestasi Siswa Menggunakan Metode K- Nearest Neighbor - Sri Siswanti, Raymundus Nandy Irawan, Wawan Laksito YS (Jurnal Ilmiah SINUS, 2013)
Decision Support System is a system that aims to provide information, guiding, giving predictions, as well as directing the user information in order to make better decisions and fact-based. The purpose of this study is to design and build a decision support applications to determine the status of student achievement using the K-Nearest Neighbor (KNN). By using the following variables: average value of Subject Education, the average value Subjects Local Content, average value self-development, and Achievement championship. The data collection methods include observation, interviews, library research methods. validation test based decision support system is that the data value of the tested students approaching the value of friends in class. Kata kunci : KNN, Php, Prestasi, Decision Support System, K- Nearest Neighbor